Evaluation of indoor air pollutants in 100 retrofit residential buildings from Romania during cold season. (20th December 2020) - Beldean-Galea, Mihail Simion; Dicu, Tiberius; Cucoş, Alexandra; Burghele, Bety-Denissa; Catalina, Tiberiu; Botoş, Marius; Ţenter, Ancuţa; Szacsvai, Kinga; Lupulescu, Alexandru; Pap, Istvan; Dobrei, Gabriel; Moldovan, Mircea; et al.
Abstract: The indoor air quality (IAQ) was in the last decades a major topic of scientific research due to evidences of adverse effects of different chemicals on the human health. The retrofit of the existing buildings in order to increase the energy performance without proper implementation may have a negative effect on IAQ. This paper is focused on a comprehensive evaluation of indoor air pollutants in 100 retrofit houses from five Romanian cities, during cold season. Radon, volatile organic compounds (VOCs) and carbonyl compounds were determined using passive samplers. At the same time, continuous, real-time monitoring of radon and carbon dioxide concentrations, as well as indoor physical parameters, such as temperature, atmospheric pressure and relative humidity was carried out. In 95% of the houses the formaldehyde concentration was higher than the guidevalue. The most present volatile organic compounds were limonene, heptane, carbon tetrachloride, tetradecane and a-pinene. A statistically significant difference in radon concentration was observed between the two sampling methods, which highlights the importance of temporal variability of indoor pollutants. High radon values were correlated with the lack of adequate ventilation, an aspect underlined by high CO2 concentrations. Additionally, the study finds that indoor air pollutants can be attributed to three main factors: the physical characteristics and usage of the indoor environment (volatile organic compounds and carbonyl compounds), the properties of the sub-slab soil (radon) and the occupational factor (CO2 ). Each factor should be treated separately when indoor air quality management is addressed. Graphical abstract: Image 1 Highlights: In 95% of houses the formaldehyde concentration was higher than the guideline value. carbonyl compounds levels were doubled compared to data recorded by other countries. 4 VOCs predominant in 83% of investigated buildings. Significant differences between radon levels in rooms with/without concrete slab. CO2 levels in moderate correlation with carbonyl compounds, radon and RH.